Quantifying dynamic range in red blood cell energetics: Evidence of progressive energy failure during storage. Issue 5 (8th April 2021) - Rogers, Stephen C.; Ge, Xia; Brummet, Mary; Lin, Xue; Timm, David D.; d'Avignon, Andre; Garbow, Joel R.; Kao, Jeff; Prakash, Jaya; Issaian, Aaron; Eisenmesser, Elan Z.; Reisz, Julie A.; et al.
Abstract: Background: During storage, red blood cells (RBCs) undergo significant biochemical and morphologic changes, referred to collectively as the "storage lesion". It was hypothesized that these defects may arise from disrupted oxygen‐based regulation of RBC energy metabolism, with resultant depowering of intrinsic antioxidant systems. Study Design and Methods: As a function of storage duration, the dynamic range in RBC metabolic response to three models of biochemical oxidant stress (methylene blue, hypoxanthine/xanthine oxidase, and diamide) was assessed, comparing glycolytic flux by NMR and UHPLC–MS methodologies. Blood was processed/stored under standard conditions (AS‐1 additive solution) with leukoreduction. Over a 6‐week period, RBC metabolic and antioxidant status were assessed at baseline and following exposure to the three biochemical oxidant models. Comparison was made of glycolytic flux ( 1 H‐NMR tracking of [2‐ 13 C]‐glucose and metabolomic phenotyping with [1, 2, 3‐ 13 C3 ] glucose), reducing equivalent (NADPH/NADP + ) recycling, and thiol‐based (GSH/GSSG) antioxidant status. Results: As a function of storage duration, we observed the following: (1) a reduction in baseline hexose monophosphate pathway (HMP) flux, the sole pathway responsible for the regeneration of the essential reducing equivalent NADPH; with (2) diminished stress‐based dynamic range in both overall glycolytic as well as proportional HMP flux. In addition, progressive with storage duration, RBCs showed (3) constraint in reducing equivalent (NADPH) recycling capacity, (4) loss of thiol based (GSH) recycling capacity, and (5) dysregulation of metabolon assembly at the cytoplasmic domain of Band 3 membrane protein (cdB3). Conclusion: Blood storage disturbs normal RBC metabolic control, depowering antioxidant capacity and enhancing vulnerability to oxidative injury.